Experiences of the Transgender and Gender Non-Conforming Community in the University Setting - Ashton Simon; Sarah Noland; Julie Krueger; Lisa Sprod (The Ohio State University Libraries, 2023)
Background: Transgender and gender non-conforming individuals face daily challenges in higher education due to a lack of gender-inclusive resources. This shortcoming is rooted in the minimal knowledge about what barriers affect this population. Aims: The aims of this study were to identify fitness-related barriers faced by the transgender community in higher education and emphasize the need to develop fitness standards for the transgender population to reduce those barriers in higher education. Methods: Participants completed one or both aspects of this study. A survey was sent to students to gather information about experiences in fitness at a university and how it relates to their gender. Several of the survey respondents then agreed to participate in a series of fitness assessments to evaluate muscular strength, endurance, and body composition. Results: Seventy-nine students responded to the survey (n = 68 cisgender females, n = 5 cisgender males, n = 2, non-binary, n = 4 transgender males). Proportionally, more transgender and non-binary people (84%) felt that gendered fitness standards did not apply to them when compared to cisgender people (31%). Further, more transgender and non-binary respondents (50%) reported that they were not comfortable working out in all areas of their gym when compared to the cisgender respondents (37%). Twenty-eight students participated in the fitness assessment. The BOD POD assessment of body composition utilizes gender to calculate body fat percentage. When using both male and female classifications, results were not different, meaning the estimated body fat percentage was calculated as the same despite a different gender in the calculation. Conclusions: This study begins to identify fitness-related barriers faced by the transgender community in higher education. Additionally, these small-scale results provide a starting point for future research on developing gender-neutral fitness standards.